V2O5 nanoparticles as cathode for lithium-ion battery applications: Fabricated via microwave-assisted green synthesis using A. paniculata leaf extract - Karthik, K. (Elsevier, 2019)
Vanadium pentoxide (V2O5) cathode was fabricated via a facile simple and microwave-assisted method by the utilization of Andrographis paniculata leaf extract as fuel and optimizes the electrochemical applications. Structural and surface morphology of V2O5 nanoparticles was analyzed by various spectroscopic techniques like SEM and TEM. The PXRD exhibits an orthorhombic crystal structure with an average crystallite size (32 nm). The band at 497 cm-1 is attributed to V-O-V stretching vibration through FTIR analysis. The electrochemical characterization of synthesized V2O5 nanoparticles was studied towards the lithium-ion battery applications. Various parameters like Charge-Discharge, Cyclic Voltammogram (CV) Columbic efficiency have performed. The V2O5 exhibits a reversible capacity of 225mAhg-1 after 50 cycles. The enhanced performance of the lithium-ion batteries is due to green synthesized V2O5 nanoparticles